Pengelolaan Konten Media Sosial Instagram pada Bisnis Kuliner @Soughdara - Safira Zakiya Putri; Anisa Diniati (Jurnal Pustaka Komunikasi, 2026)
In today's digital era, social media is an effective tool for business promotion. Improving branding can also be done through social media. The purpose of this research is to find out the management of Instagram social media content in the Soughdara culinary business. This research uses the social media planning model by Luttrell (2015) to explain the stages of managing Soughdara's Instagram social media content. This research uses a qualitative approach with a descriptive research type and data collection techniques carried out through the main source of social media monitoring results on the @soughdara Instagram account, interviews with three key informants, one expert informant, and two supporting informants, also through non-participant observation, and document studies. The results showed that the implementation of Instagram social media content management carried out by Soughdara to improve business promotion and branding on social media has been carried out optimally. The content management consists of four stages, namely the @soughdara Instagram account analysis stage, the idea and content creation stage, the account management stage, and the evaluation stage. With this implementation, Soughdara obtained a positive assessment from its followers on Instagram.